The role of self-esteem in the diminution of substance abuse among adolescents - Uba, Ikechukwu; Yaacob, Siti Nor; Abu Talib, Mansor; Abdullah, Rohani; Mofrad, Sakineh (IRSSH Research Group, 2013)
The study examined the role of self-esteem in the reduction of substance abuse among adolescents in Nigeria. A set of instruments measuring peer substance use, self-esteem and substance abuse were distributed to a sample of 352 adolescents between 13 to 18 years from secondary schools in Somolu, Lagos, Nigeria. The results confirmed the partial mediation effect of self-esteem in the relationship between peer substance use and substance abuse. The findings indicated that self-esteem plays an important role in the diminution of substance abuse among adolescents. Recommendations of the study focused on the need for researchers to explore numerous other individual, family, and school factors that maybe correlated with adolescent substance abuse as possible mediators.